Fatality and risk features for prognosis in COVID-19 according to the care approach - a retrospective cohort study. - Mariano Andrés; Jose-Manuel Leon-Ramirez; Oscar Moreno-Perez; José Sánchez-Payá; Ignacio Gayá; Violeta Esteban; Isabel Ribes; Diego Torrus-Tendero; Pilar González-de-la-Aleja; Pere Llorens; Vicente Boix; Joan Gil; et al. (PLoS ONE, 2021)
Introduction This study analyzed the impact of a categorized approach, based on patients' prognosis, on major outcomes and explanators in patients hospitalized for COVID-19 pneumonia in an academic center in Spain. Methods Retrospective cohort study (March 3 to May 2, 2020). Patients were categorized according to the followed clinical management, as maximum care or limited therapeutic effort (LTE). Main outcomes were all-cause mortality and need for invasive mechanical ventilation (IMV). Baseline factors associated with outcomes were analyzed by multiple logistic regression, estimating odds ratios (OR; 95%CI). Results Thirty-hundred and six patients were hospitalized, median age 65.0 years, 57.8% males, 53.3% Charlson index ≥3. The overall all-cause fatality rate was 15.0% (n = 46). Maximum care was provided in 238 (77.8%), IMV was used in 38 patients (16.0%), and 5.5% died. LTE was decided in 68 patients (22.2%), none received IMV and fatality was 48.5%. Independent risk factors of mortality under maximum care were lymphocytes <790/mm3, troponin T >15ng/L and hypotension. Advanced age, lymphocytes <790/mm3 and BNP >240pg/mL independently associated with IMV requirement. Conclusion Overall fatality in the cohort was 15% but markedly varied regarding the decided approach (maximum care versus LTE), translating into nine-fold higher mortality and different risk factors.